Loan Loss Provisioning Behavior: The Case of Indonesia - DENG, SUYA (2017)
Abstract The purpose of this dissertation is to investigate from 2011 to 2016 Indonesian banking sectors’ loan loss provision behavior through the data of selected 44 commercial banks. At first, we test the impact of X-efficiency on LLP, and the second step by using the GMM estimation and X-efficiency as the endogenous variables to build the LLP model, and based on the relevant literature and empirical research to get the result. We found that in Indonesia, X-efficiency actual influence the behavior of loan loss provision and by combining the significance and positive or negative coefficients, the following theories are existence: income smoothing, business cycle. Besides, since the macroeconomic variables has huge effect on LPP the size of banks, CUSTDEPTF and COST1 also as the significant factors.